The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/1678-98732230e007
|View full text |Cite
|
Sign up to set email alerts
|

Delegitimization strategies as a means of policing protesters online during the pandemic in Poland

Abstract: Introduction: This paper identifies delegitimization strategies that illustrate a range of attitudes of the Polish police towards individuals who resist the government and challenge the state legitimacy. Materials and Methods: The research is embedded in the theories of macro-strategies of delegitimization, out-casting micro-strategies, and is based on qualitative intertextual analysis of police statements in order to explain how the police responded to social opposition and shaped their relations with protes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Protesters need the police to protect a given gathering. The police do not have total control over the protest, as part of it is handed over to the protesters, who have their coordinators (Rak, 2022).…”
Section: Theoretical and Methodological Frameworkmentioning
confidence: 99%
“…Protesters need the police to protect a given gathering. The police do not have total control over the protest, as part of it is handed over to the protesters, who have their coordinators (Rak, 2022).…”
Section: Theoretical and Methodological Frameworkmentioning
confidence: 99%
“…It is worth considering that those responsible for the Framework Programme should represent different political views and be able to conduct a constructive dialogue. The protests revealed that the image of the police in the eyes of the public has also deteriorated significantly (Rak, 2022). It eventually enabled National Television to take control of them and make evaluations, to enter the role of security services.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%